Cover Image, Volume 34, Issue 2. (9th February 2018) - Amaral, S.D.; Branco, P.; Katopodis, C.; Ferreira, M.T.; Pinheiro, A.N.; Santos, J.M.
Abstract : The cover image, by S.D. Amaral et al., is based on the Research Article To swim or to jump? Passage behaviour of a potamodromous cyprinid over an experimental broad‐crested weir, DOI10.1002/rra.3232 .